The Effect of Sloping Land Conversion Program on Soil Erosion in Shaanxi Province, China: A Spatial Panel Approach - Xie, Yifan; Wang, Liye; An, Rui; Luo, Xuan; Lu, Yanchi; Liu, Yaolin; Yao, Shunbo; Liu, Yanfang (Frontiers in Environmental Science, 2022)
Soil erosion is a land degradation process that may threaten the sustainability of ecosystem as well as cause severe social and economic problems. The studies on the effect of ecological restoration policies on soil erosion have been well-documented, while the spatial relationships and spillover effects of the policies on soil erosion has been rarely scrutinized, though it’s of great policy implications in soil erosion control. Based on the analysis of the spatio-temporal evolution of soil erosion in 107 counties of Shaanxi Province with Revised Universal Soil Loss Equation (RUSLE), this study employs a panel spatial Durbin model (SDM) with multi-source data for 107 counties over 2000 to 2015 to investigate the spatial effects of the Sloping Land Conversion Program (SLCP) on soil erosion control with investment data of SLCP. The results show that during 2000-2015 the average amount of soil erosion exhibited a significant downtrend contributed by the continuous investment of SLCP. The spatial economic results demonstrate that the own effect as well as the spillover effect of investment on soil erosion control are significant and positive. A 0.1 billion CNY increase in investment in a county will result in a reduction of the total soil erosion by 288.69 thousand t/a, of which 63% is contributed to the own direct effect on local soil erosion control, and the 37% of it is contributed to the spillover effect on the neighbors. Moreover, the rainfall has a significant and positive moderating effect on the mitigation effect of SLCP on soil erosion at county scale, the marginal contribution of investment of SLCP on soil erosion control in the county with less rainfall is greater than the county with more rainfall. These findings contribute to further our understanding of the long-term effects of ecological restoration policies and transboundary ecological governance.